A circulação de práticas e ideias balneárias: a estância termal de Poços de Caldas (MG) - Lohanne Fernanda Gonçalves Ferreira (Confins, 2019)
One can say that the coastal and thermal spa models are concurrent at birth, although strongly connected by the coincident frequency of the elites who founded and frequented them. To understand some dimensions of circulation practices and spa ideas between the coast and the spas, we start from the experience of one of the main seaside cities of the early twentieth century in Brazil, Poços de Caldas (MG). In addition to the historiography built on the city, we analyze in this article the occurrences about the city in the articles of the magazine O Cruzeiro. Three moments of the resort were identified: the construction of the spa as a resort; the apogee and the consolidation of the spa from the practices; and the decline of the spa as a social space of the Brazilian elites - at the same time as the seaside resorts were gaining strength.